Use of glogster, web tool 2.0 in the communicative approach for developing oral discourse competence of third year students of Bachelor in Modern Languages French and English Specialty at the Department of Foreign Languages of the University of El Salvador during the year 2014 - Rodríguez Rosales, Karla Mercedes; García Henríquez, Juan Ricardo; Marroquín Reyes, Yenny Clarisa; Gamero Ortiz, José Ricardo; Ayala, Edgar Nicolás (San Salvador : Universidad de El Salvador, 2015)
The 21st century is primarily a decade of changes in the educational field improving and innovating with new technologies the teaching-learning process. In response to such needs, the acceptance of Glogster EDU one of the most efficient platforms for teachers and students played an important role in the Deparment of Foreign Languages in the University of El Salvador providing students a fun learning experience, increasing their motivation to organize and display their knowledge and understanding in ways that others can view, use and access. Being aware of the challenge of its implementation into the Deparment of Foreign Languages this project intended to explore the usefulness of the Glogster as a new tool in the class building on the third year students interest and involving their multiple intelligences.This research comprised some key factors such as: students and teachers’ willingness to compromise to the usage of glogsters, budget, equipment, time to create, present and check glogsters. The problematic situation in the Department of the Foreing Laguages involved the limited budget regarding the notebook equipment investment and the lack of technological training for teachers related to educational platforms.
Tesis (Licenciatura en Lenguas Modernas Especialidad en Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2015
Bibliografía : hojas 71-73
Keywords: Inglés -- Enseñanza; Glogster; Web tool 2.0